Financial Performance Causes Palm Oil Stock Prices In Indonesia To Rise? - Hilmi; Marjulin; Lilis Puspitawati; Rayyal Hayati (Jurnal Akuntansi, 2025)
The study aimed to analyse Palm Oil companies' financial performance on the Indonesia Stock Exchange 2018-2022. The independent variables were proxied in return on equity (ROE), return on assets (ROA), earnings per share (EPS) and their effect on stock prices. The population of the study was public Palm Oil companies. The sampling technique was purposive; the selected sample was 13 companies, and the total sample was 65. Data was obtained from published annual reports. Data processing used panel data regression with Eviews statistical software. The study's results showed that return on equity (ROE) and return on assets (ROA) positively and significantly affected stock prices. In contrast, earnings per share (EPS) did not affect stock prices; simultaneously, the study's results significantly affected stock prices.